Phenomenology of the SU(3)c ⊗ SU(3)L ⊗ U(1)X model with right-handed neutrinos (2007)
ABSTRACT: A phenomenological analysis of the three-family model based on the local gauge group SU(3)c⊗SU(3)L⊗U(1)X with exotic charged leptons, is carried out. Instead of using the minimal scalar sector able to break the symmetry in a proper way, we introduce an alternative set of four Higgs scalar triplets, which combined with an anomaly-free discrete symmetry, produce quark and charged lepton mass spectrum without hierarchies in the Yukawa coupling constants. We also embed the structure into a simple group and show some conditions to achieve a low gauge coupling unification, avoiding possible conflict with proton decay bounds. By using experimental results from the CERN-LEP, SLAC linear collider, and atomic parity violation data, we update constraints on several parameters of the model.